Meaningful values in the Forgotten Joint Score after total knee arthroplasty: minimal clinical important difference, minimal important and detectable changes, and patient-acceptable symptom state. (3rd May 2021) - Clement, Nick D.; Scott, Chloe E. H.; Hamilton, David F.; MacDonald, Deborah; Howie, Colin R.
Abstract : Aims: The aim of this study was to identify the minimal clinically important difference (MCID), minimal important change (MIC), minimal detectable change (MDC), and patient-acceptable symptom state (PASS) threshold in the Forgotten Joint Score (FJS) according to patient satisfaction six months following total knee arthroplasty (TKA). Methods: During a one-year period 484 patients underwent a primary TKA and completed preoperative and six-month FJS and OKS. At six months patients were asked, "How satisfied are you with your operated knee?" Their response was recorded as: very satisfied, satisfied, neutral, dissatisfied, or very dissatisfied. The difference between patients recording neutral (n = 44) and satisfied (n = 153) was used to define the MCID. MIC for a cohort was defined as the change in the FJS for those patients declaring their outcome as satisfied, whereas receiver operating characteristic curve analysis was used to determine the MIC for an individual and the PASS threshold. Distribution-based methodology was used to calculate the MDC. Results: Using satisfaction as the anchor question, the MCID for the FJS was 16.6 (95% confidence interval (CIs) 8.9 to 24.3; p < 0.001) and when adjusting for confounding this decreased to 13.7 points (95% CI 4.8 to 22.5; p < 0.001). The MIC for the FJS for a cohort of patients was 17.7 points and for an individual patient was 10 points. The MDC90 for the FGS was 12 points; where 90% of patients scoring more than this will have experienced a real change that is beyond measurement error. The PASS was defined as 22 points or more in the postoperative FJS. Conclusion: The estimates for MCID and MIC can be used to assess whether there is clinical difference between two groups and whether a cohort/patient has had a meaningful change in their FJS, respectively. The MDC90 of 12 points suggests a value lower than this may fall within measurement error. A postoperative FJS of 22 or more was predictive of achieving PASS. Cite this article: Bone Joint J  2021;103-B(5):846–854.